Human Trafficking in Indonesia: Law Enforcement Problems - Naibaho, Nathalina (UI Scholars Hub, 2011)
Human Trafficiking is considered as a crime against humanity. To conduct the due process of law towards cases related with human trafficking, the law enforcement officers cannot work by themselves. They really need assistance from many parties – such as active report from the society – as a valuable information to disclose such cases. Law enforcement conducted towards woman and child trafficking is still ineffective. It is proven by many existing cases, that low number of processed cases before the court and minimum sanction convicted to the perpetrators is clearly evident. Factors which are deemed to have correlation with low attempt of law enforcement towards legal case on this case, among others are: Lack of the Government’s commitment to fight against the crime of human trafficking, in the event that the ineffectiveness in utilization of prevailing laws and regulation; Lack of capacity of professionalism of law enforcement agency (and relevant parties) in handling women and child trafficking at the field. This may be caused by lack of knowledge on infringed regulation. For that matter, those law enforcement agency shall be given socialization and an SOP (standardized operational procedure), so that there will be no inconsistency in handling the existing cases.